2021
DOI: 10.3390/coatings11091069
|View full text |Cite
|
Sign up to set email alerts
|

Superlow Friction of a-C:H Coatings in Vacuum: Passivation Regimes and Structural Characterization of the Sliding Interfaces

Abstract: A combination of atomistic simulations and vacuum tribometry allows atomic-scale insights into the chemical structure of superlubricious hydrogenated diamond-like carbon (a-C:H) interfaces in vacuum. Quantum molecular dynamics shearing simulations provide a structure-property map of the friction regimes that characterize the dry sliding of a-C:H. Shear stresses and structural properties at the sliding interfaces are crucially determined by the hydrogen content CH in the shear zone of the a-C:H coating. Extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…In this case, the D parameters are 18.5 and 17.2 eV for the Si 3 N 4 and SiO 2 balls, respectively, i.e., larger than the D parameter recorded outside the wear scar on the a-C:H flat (D = 16.8 eV, Figure 2d). In addition, shoulder peaks around 262 eV, attributed to the presence of polymeric chains −(CH 2 −CH 2 ) n −, 23 are less pronounced inside the wear scars on the ceramic balls than inside and outside the wear scars on the a-C:H(36)-coated flats. These spectroscopic analyses confirm the presence of a carbonaceous transfer film with a thickness of a few nanometers on the ceramic surfaces and suggest sp 3 -to-sp 2 rehybridization and dehydrogenation of the transfer films.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the D parameters are 18.5 and 17.2 eV for the Si 3 N 4 and SiO 2 balls, respectively, i.e., larger than the D parameter recorded outside the wear scar on the a-C:H flat (D = 16.8 eV, Figure 2d). In addition, shoulder peaks around 262 eV, attributed to the presence of polymeric chains −(CH 2 −CH 2 ) n −, 23 are less pronounced inside the wear scars on the ceramic balls than inside and outside the wear scars on the a-C:H(36)-coated flats. These spectroscopic analyses confirm the presence of a carbonaceous transfer film with a thickness of a few nanometers on the ceramic surfaces and suggest sp 3 -to-sp 2 rehybridization and dehydrogenation of the transfer films.…”
Section: ■ Resultsmentioning
confidence: 99%
“…At first sight, these results could be ascribed solely to the number of hydrogen-passivated carbon dangling bonds, which should increase with increasing C H . However, it should be noted that the passivation of a-C:H surfaces can be effectively achieved also at low C H , for instance by localized aromatization . Both passivation mechanisms require plastic rearrangement of a-C:H during running-in .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the frequency of thermal barrier crossings is underestimated and most reactions occur via stress-induced instabilities. However, it is evident from previous studies that simulations at higher shear rates still provide useful qualitative insights into mechanochemical reactions in carbon based tribosystems 37 , 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Lugo et al [27] deposited hydrogenated DLC films using a pulsed DC PECVD system and controlled hydrogen content by altering deposition voltage and found films with high-hydrogen content (40 at.-%) have lower COF (0.014) compared with higher COF (0.38) of low-hydrogen film (25.52 ± 0.82 at.-%). Kuwahara et al [28] combined atomistic simulation and vacuum tribometry to reveal atomic-scale structure of the super-lubricated a-C:H surface during friction in vacuum. It was found that hydrogen content on the counterface plays a major role in vacuum friction.…”
Section: Research Status Of Dlc Filmmentioning
confidence: 99%